Accelerated capsular phimosis - Jain, MBBS, DNB, FICO, Tanya; Sen, MBBS, MS, Alok; Karkhur, MBBS, MS, DNB, Samendra (Digital Journal of Ophthalmology, 2020)
A 30-year-old man presented at Sadguru Netra Chikitsalaya, Chitrakoot, Madhya Pradesh, India, with diminution of vision in the right eye of 6 months’ duration. On examination, best-corrected visual acuity was 6/36 in the right eye, and intraocular pressure was 14 mm Hg. An advanced cataract was present, hindering visualization of the fundus. The left eye was phthisical, following trauma. The patient had been treated for multifocal choroiditis with panuveitis 4 years previously. He underwent cataract surgery, with implantation of single piece, rigid intraocular lens. One month postoperatively best-corrected visual acuity was 6/18; however, examination revealed anterior capsular phimosis and contracture of capsular bag with zonular stretching (A, retro-illumination). This contracture was strong enough to cause folding of the haptics (B, diffuse illumination). The patient was followed closely in anticipation of either stabilization of the progressive contracture or posterior dislocation of the capsular bag–IOL complex.